Prevalence of smoking and associated factors in people living with HIV undergoing treatment - Luciane de Souza Leal Teixeira; Maria das Graças Braga Ceccato; Wânia da Silva Carvalho; Juliana de Oliveira Costa; Palmira de Fátima Bonolo; Jullye Campos Mendes; Micheline Rosa Silveira (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To estimate the prevalence of smoking and evaluate the factors associated with this outcome in people living with HIV (PLHIV). METHODS: This is a cross-sectional study of a prospective concurrent cohort of 462 individuals initiating antiretroviral therapy at three HIV/AIDS specialized services in Belo Horizonte between 2015 and 2017. The following smoking status were used: current smoker (CS), former smoker (FS) and non-smoker (NS). Multinomial logistic regression was performed with NS as the reference category. RESULTS: Most participants were men (81.4%), young (up to 34 years old; 57.2%) and non-white (75.7%). Of the total number of individuals, 27.7% were CS, 22.9% FS, and 49.4% NS. Most smokers were light smokers (65.1%), consumed up to 10 cigarettes per day and had been smoking for more than 10 years (63.3%), starting on average at 17.2 years of age (SD = 5.1). In the multivariate analysis, higher chances of being CS were associated with: being female, having up to 9 years of schooling, current or prior use of alcohol and illicit drugs (marijuana, cocaine and crack) and presenting signs and/or symptoms of anxiety or depression. Higher chances of being FS were associated with having up to 9 years of schooling and current or prior use of alcohol and illicit drugs (marijuana and crack). CONCLUSIONS: The results show that smoking is highly prevalent among PLHIV, indicating the need for HIV specialized services to prioritize smoking cessation interventions. These interventions should consider the use of alcohol and illicit drugs and be targeted especially to young people, those with low schooling and with signs and/or symptoms of anxiety or depression.